Do immigrants take the jobs of native workers? - Nikolaj Malchow-Møller; Jakob Roland Munch; Jan Rose Skaksen (Institute for the Study of Labor (IZA), 2009)
In this paper, we focus on the short-run adjustments taking place at the workplace level when immigrants are employed. Specifically, we analyse whether individual native workers are replaced or displaced by the employment of immigrants within the same narrowly defined occupations at the workplace. For this purpose, we estimate a competing risks duration model for job spells of native workers that distinguishes between job-to-job and job-to-unemployment transitions. In general, we do not find any signs of native workers being displaced by immigrants. Furthermore, we find only very limited signs of replacement of native workers by immigrants. Instead, in particular low-skilled native workers are less likely to lose or leave their jobs when the firms hire immigrants.
urn:nbn:de:101:1-2009051383
Keywords: F22; J61; J63; 330; Immigration; adjustment costs; displacement; job spells; duration model; Internationale Arbeitsmobilität; Einwanderung; Migranten; Arbeitsmarkt; Dänemark